The (In)Stability of Residential Burglary Patterns on Street Segments: The Case of Antwerp, Belgium 2005-2016 - Vandeviver, Christophe (Journal of quantitative criminology, 2019)
To examine the spatial concentration and spatial stability of residential burglary at micro places in the context of a substantial city-level burglary drop in Antwerp, Belgium.